2005
DOI: 10.1007/s00497-005-0011-3
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of post-pollination barriers among three colour morphs of the deceptive orchid Dactylorhiza sambucina (L.) Soó

Abstract: Evidence of post-pollination barriers among three colour morphs of the deceptive orchid Dactylorhiza sambucina (L.) SoóAbstract Floral-colour polymorphism in rewardless orchids has been hypothesized to be maintained by means of naı¨ve insects, which after visiting a flower without reward will tend to fly elsewhere, looking for a flower of a different colour. In this study, levels of male and female reproductive success were monitored in Southern Italy populations of the deceptive orchid Dactylorhiza sambucina,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…Pollination is the primary step in seed set, and events starting at pollination and terminating at fertilization in wide crosses involve complex and harmonious interactions including cell-cell recognition and cellular signaling (Mascarenhas 1993;Wilhelmi and Preuss 1997;Malhó 1998;Franklin-Tong 1999;de Graaf et al 2001). Failures in pollination are thought to be widespread in plants and a common cause of low seed set (Wilcock and Neiland 2002;Marta et al 2004;Pellegrino et al 2005;Hodnett et al 2005;Ram et al 2006;Lee et al 2008;Spielman and Scott 2008). For instance, Mazzucato et al (2003) indicated that a defective pollen-pistil interaction was a main factor leading to low seed set in the parthenocarpic fruit tomato mutant.…”
Section: Discussionmentioning
confidence: 97%
“…Pollination is the primary step in seed set, and events starting at pollination and terminating at fertilization in wide crosses involve complex and harmonious interactions including cell-cell recognition and cellular signaling (Mascarenhas 1993;Wilhelmi and Preuss 1997;Malhó 1998;Franklin-Tong 1999;de Graaf et al 2001). Failures in pollination are thought to be widespread in plants and a common cause of low seed set (Wilcock and Neiland 2002;Marta et al 2004;Pellegrino et al 2005;Hodnett et al 2005;Ram et al 2006;Lee et al 2008;Spielman and Scott 2008). For instance, Mazzucato et al (2003) indicated that a defective pollen-pistil interaction was a main factor leading to low seed set in the parthenocarpic fruit tomato mutant.…”
Section: Discussionmentioning
confidence: 97%
“…Studies on species with petal‐color polymorphism also found that pollen from different variants played differential roles in male function, documenting that one morph usually had higher siring success than the others (Schoen and Clegg ; Jones ; Pellegrino et al. ,b). However, if one morph consistently outperforms the others, directional selection would favor a shift from polymorphism to monomorphism within the populations (Schoen and Clegg ; Cooley et al.…”
Section: Discussionmentioning
confidence: 99%
“…Hand pollination experiments between the three petal color morphs in Dactylorhiza sambucina showed that seed set resulting from intramorph pollination was significantly higher than that from intermorph pollination (Pellegrino et al. ). Such effects of single‐donor pollination treatments on seed production were not observed in the petal color polymorphic Dactylorhiza incarnata (Vallius et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the partial morph constancy of bumblebees, other mechanisms have been suggested as being responsible for the maintenance of colour dimorphism (or polymorphism) in D. sambucina . These include negative frequency‐dependent selection (Gigord, Macnair & Smithson, 2001) and partial post‐pollination barriers detected through differential viability and germinability of seeds from experimental crosses (Pellegrino, Bellusci & Musacchio, 2005; Jersákova, Kindlmann & Renner, 2006).…”
Section: Discussionmentioning
confidence: 99%